Alleviation of renal oxidative stress by Cassia alata in acetaminophen-induced nephrotoxic rats - Abu I.F.; Noor A.A.M.; Zulkifli A.D.; Abdullah N.; Juliana N.; Fazel M.F. (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by SCOPUS